The Second Half of The XIX Century - The Policy of Resettlement of the Russian Empire in Turkestan in the Early XX Century and its Consequences (On the example of Fergana region) - Ravshanov Sherzod Rakhmatovich (Genius Journals, 2022)
This article explores the strategic goals of the tsarist regime and the colonial nature of the resettlement policy in connection with the study of the place of the resettlement policy pursued by the Russian Empire in order to colonize Turkestan, including the Fergana region
Keywords: politics; colonial; government; population